2017
DOI: 10.1002/pen.24530
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of shrinkage and ejection forces of reinforced polypropylene based on nanoclays and short glass fibers

Abstract: This study presents the influence of nanoclays and glass fibers on the shrinkage and ejection forces of polypropylene-based composites for tubular parts produced by injection molding. An instrumented mold was used to measure cavity pressure, surface temperature and ejection forces in the tubular parts during the injection cycle. The materials used for the study were polypropylene homopolymer Domolen 1100L, nanoclays for polyolefin nanocomposites (P-802 nanoMax, used in percentages of 2%, 6%, and 10%) and reinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Processing requirements for nanofluid kaolin also limit implementation at an industrial level. The addition of nanoclays in short GFs‐polypropylene composites resulted in reduced shrinkage and decreased the ejection forces compared with GFs/PP and pure PP systems clearly indicating the benefits of combining nano‐ and micro‐size reinforcements.…”
Section: Introductionmentioning
confidence: 97%
“…Processing requirements for nanofluid kaolin also limit implementation at an industrial level. The addition of nanoclays in short GFs‐polypropylene composites resulted in reduced shrinkage and decreased the ejection forces compared with GFs/PP and pure PP systems clearly indicating the benefits of combining nano‐ and micro‐size reinforcements.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, its limited exploration as a 3D printing element allows for the novel implementation and delivery of new research elds that are not currently covered in this area; however, the thermal shrinkage of PP during printing generates poor quality [11,12]. Nevertheless, recent research has shown that it is possible to signi cantly reduce these drawbacks by applying loads while maintaining suitable mechanical characteristics [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the 'cold contraction' phenomenon of materials at CT environment will cause a certain degree of dimensional shrinkage of the composites product, 11,12 which may cause structural damage to some precision assembled devices. At present, a lot of work has shown that the injection molding process, mold temperature, filler type, crystallinity of the matrix resin and other factors have effect on the shrinkage properties of PP composites 13–16 . However, these conclusions are resulted from the application of PP composites at RT, and there are certain limitations for the application at CT.…”
Section: Introductionmentioning
confidence: 99%